The Husby Consumption Analysis: A Comment - Gapinski, James H. (The Review of Economics and Statistics, 1974)
centripetal, with a mode in the range D1 0.50 0.59, the corresponding NE being 2 1.69. The probable reason for this peak is that what had been relatively small specialist enterprises had entered one or other industry in which minimum efficient size is relatively large. As Gort (1962, p. 74) writes, successful entry (into such industries) will necessarily produce a high ratio of nonprimary to primary employment. This could lead to some bunching of values of D1 in the neighbourhood of 0.50. The evidence is consistent with this explanation, since enterprises classified to D1 0.500.59 had the lowest average size of enterprises in all of the size categories in table 5 except D1 1.